Millimeter-wave antenna array with dielectric systems of distribution and radiation - Antonov, A. S.; Afanasyev, M. A.; Savelev, V. A.; Sugak, M. I. (Proceedings of the 2014 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference : 3-5 February 2014, 2014)
Results of full-wave simulation of the millimeter-wave antenna array with feed system based on a planar dielectric waveguide are presented. The problem of a choice of the electrical properties of materials and geometry of array's elements are discussed. Results of calculation of the directivity and gain are presented.